Risk Factors and Management of Dengue Hemorrhagic Fever (DHF) in Children in 2023–2025: Literature Review) - Aullia Auffa Marthadila; Khuliyah Candraning Diyanah (Rifa'Institute, 2026)
Introduction: Dengue Hemorrhagic Fever remains a major public health problem in Indonesia, especially among children who are vulnerable to severe complications due to their immature immune systems. Objective: This study aimed to analyze the risk factors and management of Dengue Hemorrhagic Fever in children based on national studies published between 2023 and 2025. Method: This study used a literature review with a descriptive qualitative approach. Articles were collected from Google Scholar, PubMed, and Garuda databases using keywords related to Dengue Hemorrhagic Fever in children. The selection process followed the PRISMA method and resulted in five national journals that met the inclusion criteria. Result and Discussion: The findings showed that the main risk factors included low parental education, poor mosquito nest eradication practices, hanging clothes inside the house, poor nutritional status, and environmental conditions supporting mosquito breeding. Effective management strategies included the implementation of the “3M Plus” program, environmental management, vector control, health education, and early medical treatment through fluid monitoring and shock detection. Conclusions: Collaboration among healthcare workers, families, schools, and communities is important to reduce Dengue Hemorrhagic Fever incidence in children